Binder-free Ni-foam bolstered NiCo2S4/NiCo-MOF composite for enhanced supercapacitor applications - Wadhwa, Priyanka; Singh, Pratap; Saini, Robin; Jain, Karuna; Dilbaghi, Neeraj; Dhaka, Rahul Kumar; Sangwan, Neelam S.; Singh, Manoj Kumar; Kumar, Sandeep (Frontiers in Nanotechnology, 2025)
Efficient electrode materials for energy storage device fabrication are in demand to address global energy needs. In this study, novel binder-free electrodes were based on NiCo2S4 (NCS) and an Ni-Co metal–organic framework (MOF). Electrodes were engineered using a convenient dual-step solvothermal method employing nickel (Ni) foam as a current collector. The electrode material was characterized for crystallinity and crystal phase purity (pXRD), morphology (FESEM), and surface elemental profiling (XPS). Cyclic voltammetry (CV) for redox behavior analysis, galvanostatic charge–discharge (GCD) for capacitance evaluation, and electrochemical impedance spectroscopy (EIS) for charge transfer resistance were employed to investigate electrochemical performance. The composite active electrode materials NCS/NCM@NF exhibited high specific capacitance (2,150.3 F g−1) at a scan rate of 2 mV s-1, with KOH (6M) as an electrolyte. The fabricated electrode was highly reusable—approximately 89% of capacitance was retained, even after 10,000 cycles of usage (charge–discharge). The composite material has high energy density, Ed (199.6 W h kg−1), and power density, Pd (1,500.2 W kg−1). The charge transfer resistance (Rct, 790 mΩ) and solution resistance (Rs, 1.52 Ω), computed through EIS, being low, show a quick charge transfer at the interface, making the composite material suitable for supercapacitor application.